Chemically Robust Ambipolar Organic Transistor Array Directly Patterned by Photolithography. Issue 11 (5th January 2017) - Lee, Eun Kwang; Park, Cheol Hee; Lee, Junghoon; Lee, Hae Rang; Yang, Changduk; Oh, Joon Hak
Abstract : Organic ambipolar transistor arrays for chemical sensors are prepared on a flexible plastic substrate with a bottom‐gate bottom‐contact configuration to minimize the damage to the organic semiconductors, for the first time, using a photolithographically patternable polymer semiconductor. Well‐balanced ambipolar charge transport is achieved by introducing graphene electrodes because of the reduced contact resistance and energetic barrier for electron transport.